Analisis Literatur Material Energetik Berbasis Nano-Komposit untuk Propelan Hibrida pada Roket Militer - Sitompul, Robby Andreas Iskandar; Ruyat, Yayat; Setyanjana, Andre Yoan; ., Marsono (Fakultas Teknik UMSU, 2025)
This research aims to analyze the literature on nano-composite-based energetic materials that can be used in hybrid propellants for military rockets. Hybrid propellants, which combine the properties of liquid and solid propellants, offer advantages such as improved combustion control and higher energy efficiency. In this context, nano-composite materials, such as metal nanoparticles (aluminum, boron) combined with oxidizers and polymer fuels, have great potential to improve the performance of hybrid propellants. This literature review identifies how the unique properties of nano-composites, such as large surface area, high reactivity, and the ability to control particle distribution, can accelerate the combustion rate and result in higher thrust. In addition, technical challenges such as controlling nanoparticle agglomeration, thermal stability, and environmental issues are discussed. This research provides an in-depth understanding of the application of nano-composite technology in the development of hybrid propellants and demonstrates the potential of these materials to improve the performance and safety of military rocket propellants. The findings are expected to serve as a basis for further research and development of more efficient hybrid propellants in the defense field.